Design, Construction and Flight testing of a Long Endurance Fixed Wing UAV - Fayad, Mohammad; Alkurdi, Raed (My University, 2026)
This thesis outlines the design process and feasibility analysis of a long-endurance, fixed-wing UAV developed at Chalmers University of Technology. The project aims to deliver a cost effective, electrically powered platform for aerial data collection while minimising the logistical challenges of manned aviation. The initial goal was a 250 km range with an 8 kg payload. However, preliminary engineering analysis showed that the low energy density of current LiPo batteries made these targets unattainable for a small scale electric UAV. As a result, the objectives were revised through benchmarking and iterative simulations to a Max Take-Off Weight (MTOW) of 12 kg and a 100 km range at a cruise speed of 20 m/s. The methodology combined mathematical modelling in Python with aerodynamic verification in XFLR5 to identify optimal configurations. The final design includes a 2.8 m wingspan with a NACA 4412 airfoil for the main wing and a NACA 0012 profile for the T-tail empennage. A detailed CAD model was created in CATIA V5, incorporating internal rib and spar structures, a frontal hinge for component access, and segmentation to fit 3D printing build volumes. Final performance analysis shows a lift-to-drag ratio of 6.92, with the mass budget primarily allocated to a 4.5 kg airframe. The calculated range of 65.0 km and 54-minute endurance do not meet the revised 100 km target, mainly due to high power consumption and fuselage drag. Nevertheless, the study confirms the platform’s digital and structural feasibility and offers a technical foundation for future improvements in aerodynamic efficiency and material selection for research- focused UAV prototypes.
Keywords: UAV; fixed-wing drone; aerodynamics; NACA 4412; XFLR5; CATIA V5; LiPo battery; long endurance; electric propulsion; feasibility analysis